Dzień Otwarty na Uniwersytecie Przyrodniczo-Humanistycznym w Siedlcach: Open Day at the University of Natural Sciences and Humanities in Siedlce - Kołodziejczyk, Agnieszka; Suchodolski, Bartłomiej (Management and Administration Journal, 2021)
x